Política e antipolítica: anarquia contemporânea, revolta e cultura libertária - Sebastião Júnior, Acácio Augusto (2013)
Anarchy is a historical practice of confrontation with the established powers, fighting against authority and in opposition to the production of subjectication. Anarchy incites an antipolitics which assures itself by the attitude of revolt. The thesis situates the libertarian culture as a result of the production of the free life that is experienced within the fight as a practice of freedom. One of its points of potency lies in the Stirnerian critical attitude present in the formation of the associations of the unique. However, considering the current context of neoliberal governmentality, and following the analysis made by Michel Foucault, the anti-globalization movement and its inaugural practice of spectacular protests are as technologies of government changing. Among the intense monitoring and communication flows, anarchist practices are captured and incorporated as a way to invigorate the movement. Many of them feed the renewed production of theories and then become metamorphosed into modulations that extend the calls for participation in the society of control. In the agonism of forces they produce counter-spectacles such as the Black Bloc tactics and can be traversed by parresiastic attitudes like the anarchist terrorism from the late 19th century or the Greeks demonstrations from the begging of the 21th century. The fire, arisen, produces and discerns. It cuts through conducts and counter-conducts as an anti-conduct of the libertarian culture including inside the anarchisms. The research emphasized this moving production of freedom and securitizations amid the Greek fire since December 2008 and its aftermath in the contemporary anarchy. It realizes that state terror does not cease, as well terrorisms. Anti-conducts emerge unexpected, imperceptible, minors, as expressions of the libertarian culture taken as revolt